A low-cost yet accurate approach to a vehicle location tracking system - Abdul Rahman, Abdul Wahab; Tan, Eng Chong; Ngiam, Chong Wah; Ong, Swee Eng; Wong, Kin Keong (1997)
This paper describes a real-time vehicle location tracking system which uses the current technology of Global Positioning System (NAVSTAR GPS) to provide continuous position and velocity tracking of a moving vehicle. This system consists of two parts - the hardware GPS tracking unit and the front-end user-friendly mapping software. The hardware-tracking unit will provide a common interface to the computer running the mapping software developed under Microsoft Windows. Eventually, the entire system will be compact and portable enough to be mounted in the vehicle for positionhelocity tracking and hence the display of tracking information on the mapping software showing the Singapore roadmaps.